2010
DOI: 10.1016/j.molcel.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The ISG15 Conjugation System Broadly Targets Newly Synthesized Proteins: Implications for the Antiviral Function of ISG15

Abstract: Summary ISG15 is an interferon-induced and anti-viral ubiquitin-like protein (Ubl). Herc5, the major E3 enzyme for ISG15, mediates the ISGylation of over 300 proteins in interferon-stimulated cells. In addressing this broad substrate selectivity of Herc5, we found that: 1) the range of substrates extends even further and includes many exogenously expressed foreign proteins, 2) ISG15 conjugation is restricted to newly synthesized pools of proteins, and 3) Herc5 is physically associated with polyribosomes. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
363
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(382 citation statements)
references
References 45 publications
17
363
1
1
Order By: Relevance
“…This mechanism is consistent with recent reports that ISG15 conjugation targets newly synthesized proteins and hence occurs on polyribosomes (22). However, in human cells transfected with a plasmid expressing the NS1B protein, and also in influenza B virus-infected human cells, the NS1B protein relocalizes essentially all the ISG15 from the cytoplasm to intranuclear compartments known as splicing or S35 speckles (16,25).…”
Section: Ns1b-ntr-b Hb/sb Vdw Isg15-c Ns1b-ntr-supporting
confidence: 91%
See 2 more Smart Citations
“…This mechanism is consistent with recent reports that ISG15 conjugation targets newly synthesized proteins and hence occurs on polyribosomes (22). However, in human cells transfected with a plasmid expressing the NS1B protein, and also in influenza B virus-infected human cells, the NS1B protein relocalizes essentially all the ISG15 from the cytoplasm to intranuclear compartments known as splicing or S35 speckles (16,25).…”
Section: Ns1b-ntr-b Hb/sb Vdw Isg15-c Ns1b-ntr-supporting
confidence: 91%
“…A predicted model of the ISG15-UbE1L complex (2) also locates the E1 conjugating enzyme in a region of the ISG15 C-terminal domain that is distant from the NS1B-binding sites in the N-terminal and linker domains of ISG15 identified in our crystal structure. In addition, the C-Ubl by itself also supports efficient ISG15 conjugation in human cells, as assayed by transfection experiments (22), showing that the N-Ubl has little or no role in the conjugation steps catalyzed by not only the E1 and E2 enzymes but also the E3 (Herc5) ligase. This result indicates that the Herc5 enzyme may be expected to function with the C-Ubl in an ISG15: NS1B complex, but this prediction cannot be tested at present because a functional Herc5 enzyme is not currently available.…”
Section: Ns1b-ntr-b Hb/sb Vdw Isg15-c Ns1b-ntr-mentioning
confidence: 98%
See 1 more Smart Citation
“…The ISGylation process targets more than 300 substrate proteins that includes a large number of constitutively expressed proteins regulating diverse cellular pathways such as RNA splicing, chromatin remodeling/polymerase II transcription, cytoskeleton organization and regulation, stress responses, and translation (Durfee et al, 2010). Hence a deregulation in the expression of ISG15 may be expected to promote carcinogenesis as ISGylated proteins remain stabilized for a sustained period.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, HDAC6 can restrict viral spread by interacting with interferon-stimulated gene 15 (ISG15) and ISG15-linked proteins, targeting them for selective autophagic degradation [112]. Previous work has demonstrated that ISG15 knockout mice are broadly susceptible to RNA and DNA viruses [113]. More detailed study has shown that ISG15 could broadly conjugate IFN-induced ISGs and viral proteins, mediating their degradation during the process of virion egress and release.…”
Section: Controlling Antiviral Immune Responsesmentioning
confidence: 99%